An evaluation of the disaster management plan of the selected libraries in Quezon City and recommendations towards the next five (5) years - Cruzata, Ivy S. (2015)
The study evaluated the existing disaster management plan of the six academic libraries in Quezon City based on National Disaster for Risk Reduction Management Council (NDRRMC) framework for disaster management. The six academic libraries in Quezon City are, Far Eastern University- Nicanor Reyes Memorial Foundation Library (FEU-NRMF), National College of Business Administration (NCBA), STI College - Fairview Campus (STI), AMA Computer University - Fairview Campus (AMACU), Our Lady of Fatima University - Fairview Campus (OLFU) Polytechnic University of the Philippines Commonwealth Campus (PUP).